PENGARUH PEMBIAYAAN SYARIAH TERHADAP PEMBERDAYAAN USAHA MIKRO KECIL DAN MENENGAH (UMKM) DI KELURAHAN PASAR BARU MUARA BULIAN - Sarfela Sarfela; Mashudi Haryanto; Alfazri Rahmadani (JOURNAL SAINS STUDENT RESEARCH, 2025)
Suharto stated that empowerment is a social work and humanitarian activity that has long received deep attention regarding the condition of poor communities. Empowerment of Micro, Small, and Medium Enterprises (MSMEs) involves a series of efforts aimed at increasing the capacity, capability, and competitiveness of MSME actors. The goal is for MSMEs to develop independently, sustainably, and contribute positively to the economy. However, problems observed in the field indicate that MSME empowerment in Pasar Baru Subdistrict is still not optimal, as MSME actors have not fully implemented sharia principles. In fact, MSME empowerment has not yet been effectively carried out. This study aims to determine and analyze whether sharia financing directly influences MSME empowerment. This research uses a quantitative method, conducted on a specific population and sample. The population comprises 60 MSMEs in Pasar Baru Subdistrict as respondents. The sample used in this research consisted of 71 MSMEs in Pasar Baru Subdistrict. Data collection was carried out through questionnaires and documentation. Data analysis was performed using multiple regression analysis with the help of SPSS version 25. The results of this study conclude that: (1) The influence of sharia financing on the empowerment of micro, small, and medium enterprises (MSMEs) is 7.75%. The calculation of t-count obtained t = 87.425 and t-table = 3.653, indicating the rejection of H0 and acceptance of H1. This means there is a significant influence of the sharia financing variable on the empowerment of MSMEs.